Radiotherapy of prostate cancer: impact of treatment characteristics on the incidence of second tumors - Milly BUWENGE; Erica SCIROCCO; Francesco DEODATO; Gabriella MACCHIA; Maria NTRETA; Silvia BISELLO; Giambattista SIEPE; Savino CILLA; Anna Rita ALITTO; Vincenzo VALENTINI; Lidia STRIGARI; Alessio G. MORGANTI; et al. (BMC Cancer, 2020)
Abstract Background It has been hypothesized that radiotherapy (RT) techniques delivering radiations to larger volumes (IMRT, VMAT) are potentially associated with a higher risk of second primary tumors. The aim of this study was to analyse the impact of RT technique (3D-CRT vs IMRT/VMAT) on the incidence of second tumors in prostate cancer (PCa) patients. Methods A retrospective study on 2526 previously irradiated PCa patients was performed. Patients were treated with 3D-CRT (21.3%), IMRT (68.1%), or VMAT (10.6%). Second tumors incidence was analysed in 3 categories: pelvic, pelvic and abdominal, and “any site”. The correlation with RT technique was analysed using log-rank test and Cox’s proportional hazard method. Results With a median follow-up of 72 months (range: 9–185), 92 (3.6%) cases of second tumors were recorded with 48 months (range: 9–152) median interval from RT. Actuarial 10-year second tumor free survival (STFS) was 87.3%. Ten-year STFS in patients treated with 3D-CRT and IMRT/VMAT was 85.8 and 84.5%, respectively (p: .627). A significantly higher 10-year cumulative incidence of second tumors in the pelvis was registered in patients treated with IMRT/VMAT compared to 3D-CRT (10.7% vs 6.0%; p: .033). The lower incidence of second pelvic cancers in patients treated with 3D-CRT was confirmed at multivariable analysis (HR: 2.42, 95%CI: 1.07–5.47, p: .034). Conclusions The incidence of second pelvic tumors after RT of PCa showed a significant correlation with treatment technique. Further analyses in larger series with prolonged follow-up are needed to confirm these results.